2016
DOI: 10.1080/13683500.2016.1273883
|View full text |Cite
|
Sign up to set email alerts
|

Travel information online: navigating correspondents, consensus, and conversation

Abstract: Travel information exists in paper guides, word of mouth, and countless websites. Organizing a trip has never been more accessible and simultaneously riddled with doubt. Professional journalists produce travel journalism while often anonymous reviewers on TripAdvisor provide their commentaries, and in between, there are blogs, wikis, tourism boards, vendors, and a host of other information sources available. How does the twenty-first-century tourist make sense of all of this information? \ud \ud Through a stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
5
19
1
1
Order By: Relevance
“…This is especially true in regard to their ability to provide up-to-date information (Fujii et al, 2016;Peel & Sørensen, 2016a;Tan & Chen, 2012). Being able to trust an information source is fundamental for tourists, and most people develop criteria or strategies to assess credibility, such as combining multiple media, double checking information, and identifying indicators of trust, such as the quality of writing or the authorship of the content (Pirolli, 2018).…”
Section: Guidebooks As a Channel For Tourism Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is especially true in regard to their ability to provide up-to-date information (Fujii et al, 2016;Peel & Sørensen, 2016a;Tan & Chen, 2012). Being able to trust an information source is fundamental for tourists, and most people develop criteria or strategies to assess credibility, such as combining multiple media, double checking information, and identifying indicators of trust, such as the quality of writing or the authorship of the content (Pirolli, 2018).…”
Section: Guidebooks As a Channel For Tourism Informationmentioning
confidence: 99%
“…More recent research has shown that the use of online channels for information search may lead to a phenomenon called online confusion, where Internet users feel overloaded with information when browsing online (Lu et al, 2016;Zillinger, 2019). However, the underlying idea is still that information seekers have strategies to overcome confusion, for example by relying on familiar information sources online, or delegating the task and search for additional information (Lu et al, 2016;Pirolli, 2018).…”
Section: The Digitalisation Of Tourism Information Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…But this search for information must be based on the trustworthiness of the media and sources. Although some users are afraid of biased information, false comments (Hensel and Deis, 2010), and have trouble determining whether to believe official websites or users reviews (Ruzic and Bilos, 2010)s, 2010), the reality is that they trust social media (Pirolli, 2018) because consumers do not make reservations before searching for online advice or information (Kim, Chung and Lee, 2011;Xiang and Gretzel, 2010).…”
Section: Trustworthiness In the Use Of Social Media And Social Networkmentioning
confidence: 99%
“…The integration of the Internet in the travel and tourism industry is a challenge for the traditional role of travel agencies (Law, Law, & Wai, 2002;Pirolli, 2016). Travel agencies are classified in retail and wholesale (Hernández & Hernández, 1998), depending on the volume and quantity of the tourist package they offer (in this research the wholesaler is studied).…”
mentioning
confidence: 99%